Insect Pests of Leguminous Forest Tree Seed and their Control - Singh, Pratap; Bhandari, R. S. (Indian Forester, 1988)
Lellumlnous tree Species are important in social forestry and wasteland development programmes’ hence there is a great demand for their seeds. For raising large nursery stock’ huge quantities of sound seed is required. But seed entomology of the leguminous tree seeds has long been a neglected subject. These seeds are often liable to be destroyed by insects. A large number of insects belonging to orders’ Coleoptera’ Lepidoptera feed on pods and seeds in nature and during storage. Most important of these are bruchid beetles of the genera Caryedon. Bruchidius and Bruchus. In most of the cases insect attack commences from the tree itself. Larvae of tortricids pyralids’ gelechids and heliodenlds also cause considerable damage to pods and seeds. Short account of these injurious insects feeding on lenguminous seeds and their control measures are given in this paper. The fight against bruchids which often destroy more than half of the seeds has been unsuccessful so far because it has not been based on adequate knowledge of the biologY of these beetles aud in particular of how they infest leguminous seeds at harvest time’ most of them are wrongly believed to attack only stored seeds. Entomologists must remedy the situation if rurther advances are to be made in social forestry and wasteland development.